Cannabinoid 1 Receptor Signaling on Hippocampal GABAergic Neurons Influences Microglial Activity - Ativie, Frank; Komorowska, Joanna A.; Beins, Eva; Albayram, Önder; Zimmer, Till; Zimmer, Andreas; Tejera, Dario; Heneka, Michael; Bilkei-Gorzo, Andras (Frontiers in Molecular Neuroscience, 2018)
Microglia, the resident immune cells of the brain, play important roles in defending the brain against pathogens, but chronic or excessive pro-inflammatory response of the microglia damages the neurons, therefore their activity is tightly regulated. Pharmacological and genetic studies showed that cannabinoid type 1 (CB1) receptor activity influences microglial activity, although the microglial CB1 receptor expression is very low. The CB1 receptors are mainly expressed on neurons in the central nervous system - on an especially high level on GABAergic interneurons. Here, we asked whether CB1 signalling on this neuronal cell type plays a role in regulating microglial activity. Therefore, we compared microglia density, morphology and cytokine expression in wild-type and GABAergic neuron-specific CB1 knockout mice (GABA/CB1-/-) under control conditions (saline-treatment) and after 3 h, 24 h or repeated LPS-treatment. Our result revealed that hippocampal microglia from saline-treated GABA/CB1-/- mice resembled those of LPS-treated wild-type animals: enhanced density and larger cell bodies, while the size and complexity of their processes was reduced. No further reduction in the size or complexity of microglia branching was detected after LPS-treatment in GABA/CB1-/- mice, suggesting that microglia in naïve GABA/CB1-/- mice were already in an activated state. This result was further supported by correlating the level of microglial TNFα with their size. Acute LPS-treatment elicited in both genotypes similar changes in the expression of pro-inflammatory cytokines. However, TNFα expression was still significantly elevated after repeated LPS-treatment in wild-type but not in GABA/CB1-/- mice, indicating a faster development of LPS tolerance. We also tested the possibility that the altered microglia activity in GABA/CB1-/- animals was due to an altered expression of neuron-glia interaction proteins. Indeed, the level of fractalkine (CX3CL1), a neuronal protein involved in the regulation of microglia, was reduced in hippocampal GABAergic neurons in GABA/CB1-/- mice, suggesting a disturbed neuronal control of microglial activity. Our result suggests that CB1 receptor agonists can modulate microglial activity indirectly, through CB1 receptors on GABAergic neurons. Altogether, we were able to demonstrate that GABAergic neurons, have a specific role in the regulation of microglial activity and cannabinoid signalling plays an important role in this arrangement.